2014
DOI: 10.5713/ajas.2014.14140
|View full text |Cite
|
Sign up to set email alerts
|

Energy Requirements in Early Life Are Similar for Male and Female Goat Kids

Abstract: Little is known about the gender differences in energetic requirements of goats in early life. In this study, we determined the energy requirements for maintenance and gain in intact male, castrated male and female Saanen goat kids using the comparative slaughter technique and provide new data on their body composition and energy efficiency. To determine the energy requirements for maintenance, we studied 21 intact males, 15 castrated males and 18 females (5.0±0.1 kg initial body weight (BW) and 23±5 d of age)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 15 publications
2
18
1
Order By: Relevance
“…Although the knowledge of the partial efficiencies of the use of the ME for NE can improve our understanding of the energy partition for growing animals, few studies have reported a k g for goats (Bompadre et al, 2014;Fernandes et al, 2007;Tovar-Luna et al, 2007), whose value varied from 0.42 to 0.60. In this study, the k g was calculated as 0.39 (Eq.…”
Section: Variablementioning
confidence: 98%
See 1 more Smart Citation
“…Although the knowledge of the partial efficiencies of the use of the ME for NE can improve our understanding of the energy partition for growing animals, few studies have reported a k g for goats (Bompadre et al, 2014;Fernandes et al, 2007;Tovar-Luna et al, 2007), whose value varied from 0.42 to 0.60. In this study, the k g was calculated as 0.39 (Eq.…”
Section: Variablementioning
confidence: 98%
“…This recommendation was based on studies using empirical models to assess the requirements by regressing intake of metabolizable energy or protein against response, such as body weight change (Sahlu et al, 2004). Because the nutritional requirements for gain are directly related to body composition, Lofgreen and Garrett (1968) proposed the comparative slaughter technique, which can address net requirements and is largely used to establish nutritional guidelines for cattle (NRC, 2000); however, few studies with goats have utilized this method (Fernandes et al, 2007;Bompadre et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In both trials, the experimental diet (Table 1) consisted of dehydrated whole corn plants (prepared as described by Bompadre et al, 2014), cracked corn grain, soybean meal, soybean oil, limestone, and a mineral supplement, which were fed as a total mixed ration at 46.2, 30.9, 15.2, 1.9, 1.0, and 4.8% of dry matter (DM), respectively. The feed ingredients were dried at 55 °C for 72 h, ground through a 1-mm screen using a Wiley mill (Arthur H. Thomas Co., Philadelphia, PA), and analyzed for ash ( To determine the NP m , 55 goats were used: 18 intact males (30.3±0.88 kg of body weight, BW), 21 castrated males (30.2±0.73 kg of initial BW), and 16 females (29.9±0.34 kg of initial BW).…”
Section: Methodsmentioning
confidence: 99%
“…A data set that included reference, qualifying (e.g., sex, level of intake, and block), and necessary quantitative data were gathered from 7 comparative slaughter studies (Gomes, 2011;Bompadre et al, 2014;Medeiros et al, 2014;Almeida et al, 2015;Ferreira et al, 2015;Figueiredo et al, 2016Figueiredo et al, , 2017. Quantitative information included days on feed, initial and final BW, empty BW (EBW), DMI, metabolizable energy intake (MEI), and body composition for each individual animal.…”
Section: Data Collectionmentioning
confidence: 99%
“…Different feeding systems indicate that intact males require more ME M 273 than females (ARC, 1980;CSIRO, 1990;NRC, 2000NRC, , 2007. Conversely, individual studies conducted with goats have generally concluded that sex affects energy requirements for growth, but it does not affect energy requirements for maintenance (Ash and Norton, 1987;Bompadre et al, 2014;Almeida et al, 2015;Figueiredo et al, 2017). Therefore, contradictory results have been reported.…”
Section: Introductionmentioning
confidence: 99%